2005
DOI: 10.2110/palo.2003.p03-99
|View full text |Cite
|
Sign up to set email alerts
|

Jurassic Dinosaur Footprints from Southern Italy: Footprints as Indicators of Constraints in Paleogeographic Interpretation

Abstract: Three loose blocks, rich in dinosaur footprints, were found in a small pier at Mattinata (Gargano Promontory, Foggia, Italy), most probably quarried from the Upper Jurassic Sannicandro Formation. All of the footprints in the blocks are ascribed to medium-sized theropod trackmakers. Recent track discoveries from both the Early Cretaceous San Giovanni Rotondo Limestone and the Late Cretaceous Altamura Limestone, as well as this new discovery, reveal the consistency of terrestrial associations along the southern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
4

Year Published

2009
2009
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 30 publications
1
25
0
4
Order By: Relevance
“…The preservation of fossil vertebrate tracks in laminated sediments, in particular in tidal-flat environments, is frequently explained by the presence of microbial mats, which are thought to have covered and stabilized the tracks (e.g, Thulborn, 1990;Avanzini, 1998;Kvale et al, 2001;Freytet, 2003;Conti et al, 2005;Marty, 2005). It has also been suggested that undertracks commonly form in well-laminated microbially-bound sediment (Lockley, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The preservation of fossil vertebrate tracks in laminated sediments, in particular in tidal-flat environments, is frequently explained by the presence of microbial mats, which are thought to have covered and stabilized the tracks (e.g, Thulborn, 1990;Avanzini, 1998;Kvale et al, 2001;Freytet, 2003;Conti et al, 2005;Marty, 2005). It has also been suggested that undertracks commonly form in well-laminated microbially-bound sediment (Lockley, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Probably due to this poor description, the ichnogenus has only been occasionally mentioned later in literature (e.g. Conti et al, 2005). However, it was later used as integrating the ichnofacies of Megalosauripus-Therangospodus for transgressive facies with tidal influence in the Jurassic of USA (Lockley et al, 2007).…”
Section: Systematic Discussionmentioning
confidence: 99%
“…Fossil footprints preserved in the Apulian platform deposits are often poor in fine anatomical detail (Nicosia et al, 2000a, b;Conti et al, 2005;Petti et al, 2008;Sacchi et al, 2009) and the BiC material is also suboptimal. With the BiC trackway it is possible to identify a potential trackmaker to a high taxonomic rank.…”
Section: Discussionmentioning
confidence: 99%
“…Five Cretaceous dinosaur track sites have been discovered so far on the Apulian carbonate Platform (Nicosia et al, 2000a,b;Conti et al, 2005;Petti et al, 2008Petti et al, , 2009Sacchi et al, 2009), most of which are associated with the Lower Cretaceous deposits of the Calcare di Bari Fm. A diverse ichnocoenosis is recorded here: it includes sauropods, theropods, ornithopods and ankylosaurs.…”
Section: Introductionmentioning
confidence: 99%